Cyclic Group Of Rational Functions With Coefficients As Fibonacci Numbers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Group theory is main topic modern algebra and group is also useful in many other fields. In this paper we show a special type relationship between group theory and number theory. In this paper will give type group of rational functions with coefficients as Fibonacci number with respect composition of mapping operation. We also show that is not only a group but also a cyclic group. In this represent a special relation between properties of group and rational functions with Fibonacci numbers coefficients. In this paper we gave a special type of recurrence relation sequence of rational functions with coefficients as Fibonacci numbers and also we proved the collection of all such rational function form a cyclic group with respect to the composition of function operation. In this represent a special relation between properties of group and rational functions with Fibonacci numbers coefficients. In this paper we gave a special type of recurrence relation sequence of rational functions with coefficients as Fibonacci numbers and also we proved the collection of all such rational function form a cyclic group with respect to the composition of function operation.